Corrosion issues in light water reactors : stress corrosion cracking - Féron, D.; Olive, J.-M (Woodhead Publishing in materials., 2007)
Stress corrosion cracking is a major problem in light water nuclear reactors, whether pressurised water reactors (PWRs) or boiling water reactors (BWRs). The nuclear industry needs to be able to predict the service life of these power plants and develop appropriate maintenance and repair practices to ensure safe long term operation. This important book sums up key recent research on corrosion in light water reactors and its practical applications. The book is divided into four parts. It begins with an overview of materials degradation due to stress corrosion, corrosion potential monitoring and passivation. Part two summarises research on susceptibility of materials to stress corrosion cracking and the ways it can be initiated. The third part of the book considers stress corrosion crack propagation processes whilst the final part includes practical case studies of corrosion in particular plants. The book reviews corrosion in a range of materials such as low alloy steels, stainless steels and nickel-based alloys. With its distinguished editor and team of contributors, Corrosion issues in light water reactors is a standard work for the nuclear industry. Summarises key recent research on corrosion in light water reactorsIncludes practical case studies.